Effect of Comparison of Sweet Potato (Ipomoea batatas L.) with Tapioca (Manihot utilissima POHL.) and Egg Concentration on Characteristics of Sweet Potato Snack - Lani Nurlela (Central Research Institute For Agriculture, 2023)
The purpose of this research is to determine the extent of the influence of the ratio between the sweet potato (Ipomoea batatas L.) with tapioca (Maniho tutilissima POHL. ) and the concentration of the eggs so that the sweet potato snack produced good characteristic. The benefit of this research is to increase the economic value of sweet potato, as the use of food product diversification, utilization of sweet potato as a snack raw material so as to created economy productive. The experiment design used in this research is a randomized block design (RAK) with 3x3 factorial three times repeated, followed by Duncan’s test. Variables experimental consisted of sweet potato comparison with tapioca (U) with variations 1:1, 1:1, 2:1 and the concentration of eggs (T) with a variation of 5%, 10%, 15%. Response in this research include water content, starch content, protein content, fat content, volume expansion and organoleptic test for color, scent, taste and crispness. The results showed that the ratio of sweet potato with tapioca impact on volume expansion, water content, starch content, and the taste of sweet potato snack. The eggs in concentration effect on protein content, taste and crispness sweet potato snack. Interaction comparison with tapioca and the egg concentrations effect on the color of sweet potato snack. u1t1 treatment ( sweet potato with tapioca amounting to 1: 1 and the egg concentration of 5%) gave the best results with the sample a water content of 7.49%; the starch content of 36,29%, 2,44% protein content, fat content of 20,24% and amounted to 192,15% volume expansion.